Discourse Markers in Nate Bargatze’s Extended Interview on CBS Sunday Morning - Anggi Cahyani Pramudita; Christianti Tri Hapsari (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study aimed to analyze the use of discourse markers (DMs) in a media interview titled Extended Interview: Comedian Nate Bargatze, published on the CBS Sunday Morning YouTube channel. The focus of this study is to identify discourse markers in the interview and classify them based on type and function. A qualitative descriptive method was employed, with data collected from the transcript of the interview video. The data were analyzed using Fraser’s (2009) framework to identify discourse marker types and Crible and Degand’s (2019) framework to examine their functions. The findings show that three types of discourse markers, which are elaborative, inferential, and contrastive marker, were found a total of 413 times. Elaborative markers appeared most frequently, with 224 occurrences, followed by inferential markers with 92 occurrences and contrastive markers with 56 occurrences. Furthermore, eight discourse marker functions were identified: addition, consequence, reduction, contrast, temporal, condition, alternative, and concession. In conclusion, discourse markers in interviews play an important role in maintaining coherence, organizing conversation, and sustaining the flow of interaction. Keywords: Discourse Markers, Media Interview, Spoken Discourse